Fracture behavior of random distributed short tungsten fiber-reinforced tungsten composites. (4th July 2019) - Mao, Y.; Coenen, J.W.; Riesch, J.; Sistla, S.; Almanstötter, J.; Reiser, J.; Terra, A.; Chen, C.; Wu, Y.; Raumann, L.; Höschen, T.; Gietl, H.; et al.
Abstract: In future fusion reactors, tungsten is considered as the main candidate material for plasma-facing components. However, the intrinsic brittleness of tungsten is of great concern during operation. To overcome this drawback, tungsten fiber-reinforced tungsten composites (Wf /W) are being developed relying on extrinsic toughening principles. Tungsten (W) fibers with extremely high tensile strength and ductility are used to reinforce a tungsten matrix. In this work, field assisted sintering technology (FAST) is used to produce Wf /W material. Mechanical characterizations including Charpy impact and 3-point bending tests are performed. Based on the 3-point bending test results, the Wf /W materials can facilitate a promising pseudo-ductile behavior even at room temperature, similar to fiber reinforced ceramic composites. Fracture energy density and fracture toughness together with the crack-resistance curves ( R -curves) are measured. Compared to conventional pure tungsten, Wf /W shows significant improvement in fracture toughness.